Failure evaluation of filament wound composite risers with isotropic liner - Boon, Yi Di (2018)
The use of composite materials such as carbon/epoxy for the construction of deep water risers in place of metals can lead to significant weight reduction and cost savings. In order to realize this potential, a thorough understanding of the mechanical behavior and failure modes of composite risers is required. In this study, the progressive damage analysis technique and finite element simulations are used extensively to investigate the failure of composite risers. The nonlinear behavior of composites in the pre-failure stage is taken into consideration in the bimodulus-plastic model developed in this study. The inclusion of the nonlinear behavior can result in better predictions in the finite element simulations. A predictive model is also developed to determine the tensile properties of composite materials affected by moisture. The model is based on the use of additive group contributions for polymers. The tensile properties calculated using the model agreed well with experimental data. The effect of moisture on the compressive properties of composite materials is also investigated in experiments and simulations. Failure at the liner-composite interface is also considered in this study. The failure and damage mechanisms at the interface for the grooving and grit blasting mechanical surface treatment methods are investigated and discussed. The behavior and failure of the liner-composite interface are modeled successfully in finite element simulations. The local analysis of a composite riser segment using finite element simulations is demonstrated. The progressive damage analysis method is effective in predicting failure, especially for cases where damage due to accidental load has occurred.